Smart Cities and Affective-Symbolic Urbanism: A Dual Tourist/Resident Perspective - Nikolaos Iason Koufodontis; Eleni Gaki; Stella Zounta (Tourism and Hospitality, 2025)
This study examines how individuals engage with smart city technologies (SCTs) through the dual roles of residents and tourists. Drawing on a new conceptual framework of affective-symbolic engagement, it explores not only adoption patterns but also users’ emotional responses and perceived inclusion. A quantitative analysis of 194 respondents reveals that while adoption rates are similar across roles, residents and tourists differ in usage routines, usability experiences, and sensitivity to symbolic cues. Tourists report more interface challenges and rely on third-party sources, while residents engage more with civic platforms. Age predicts usability barriers, but education does not significantly affect engagement. Emotional comfort and symbolic belonging are shaped less by demographic background and more by situational role and perceived design inclusivity. The findings extend smart city theory by incorporating role-sensitive, affective, and symbolic dimensions of digital engagement and support policies aimed at inclusive, human-centered urban technologies.